A STUDY ON COAL ASH IN REINFORCED CONCRETE BEAMS REPLACED WITH FINE AGGREGATES - Suganya, B.; Nizar, N.Mohamed (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Now a day’s the availability of aggregates decreases so we have decided to replacement of fine aggregates and partial replacement of cement with coal ash. A comparative analysis of the experimental results of the properties of fresh and hardened concrete with full replacement of fine aggregates with quarry dust and also partially replacing cement with varying ratio of coal ash is to be carried out in this project. Five types of concrete mixtures were tested concrete made entirely with natural aggregate concrete (NAC) as a control concrete and four types of concrete made with varying ratio of coal ash ( 10%, 20%, 30%,40% ). Five specimens were made for the testing of the basic properties of hardened concrete. Load testing of reinforced concrete beams made of the investigated concrete types is also to be carried out in this project